2020
DOI: 10.3390/ma13010212
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Stabilization Systems and Multiple Ultraviolet A (UVA) Aging/Recycling Steps on Physicochemical, Mechanical, Colorimetric, and Thermal-Oxidative Properties of ABS

Abstract: Commercially mass-polymerized acrylonitrile–butadiene–styrene (ABS) polymers, pristine or modified by stabilization systems, have been injection molded and repeatedly exposed to ultravilolet A (UVA) radiation, mechanical recycling, and extra injection molding steps to study the impact of such treatments on the physicochemical, mechanical, colorimetric, and thermal-oxidative characteristics. The work focus on mimicking the effect of solar radiation behind a window glass as relevant during the lifetime of ABS po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…These experimental TGA curves confirm that UMIM modifies the material molecular structure, which agrees with the findings of Refs. [ 9 , 10 ]. The specimen section C (the furthest from injection gate) developed properties very similar to those of the virgin pellets, while the material located close to section A, experience the highest molecular weight loss.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These experimental TGA curves confirm that UMIM modifies the material molecular structure, which agrees with the findings of Refs. [ 9 , 10 ]. The specimen section C (the furthest from injection gate) developed properties very similar to those of the virgin pellets, while the material located close to section A, experience the highest molecular weight loss.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that antioxidants added in sufficient amount during the original material processing reduce thermal-oxidative degradation improving the recycled material physical and chemical properties. In addition, Fioro et al [ 9 ] studied ABS polymer degradation with different stabilization systems and repeatedly exposed the injected molded parts to ultraviolet A radiation, and mechanical recycling, in order to investigate the impact of these treatments on the physicochemical, thermo-oxidative, and mechanical properties. They found that mechanical recycling increases the injected molded parts strain at break with a slight decrease in the tensile modulus.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer materials are currently widely used in many industries, such as medical, electronics, automotive and building [ 1 , 2 ]. The popularity of polymers is associated with relatively low prices, a very good price-quality ratio and general availability [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The selection of the right production structure is the key polyethylene terephthalate (PBT), polyacetal (POM), etc. [35][36][37]. In addition, polymer composites can be used for various parts of a vehicle body or, for example, gearbox housings [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%